The dynamics shaping Turkish African Policy and Turkey’s Approach towards the Western Sahara Conflict - Sıradağ, Abdurrahim (Africana Studia, 2020)
This research examines the factors and the dynamics that shape Turkish Foreign Policy (TFP) towards Africa. The study highlights the five important factors affecting TFP in Africa. The first factor is that Turkey’s historical legacy has paved the way for strengthening relations with Africa. The second factor is that the changing domestic dynamics in Turkey have been significant driving forces to engage with the African continent. The third dynamic is a new geopolitical balance of power emerged in the region of the Middle East and North Africa (MENA) after 2011 that forced Turkey to look for new economic and political allies in Africa. The last factor is the impact of globalization. Due to the process of globalization, Turkish NGOs, think tanks, and economic associations have become more active players in shaping TFP towards Africa. This research also explains Turkish foreign policy approach towards the Western Sahara conflict. Turkey’s strong economic and political relations with Morrocco has limited Turkey’s active involvement towards the Western Sahara conf lict. Furthermore, the many actors’ involvement in the conflict undermines Turkey’s engagement in the Western Sahara. Keywords: Turkey, Africa, Turkish foreign policy, Western Sahara conflict.